2020
DOI: 10.3390/su12093823
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Nature Experiences Involving Wolves on YouTube: Presence, Emotions, and Attitudes in Immersive and Nonimmersive Settings

Abstract: As some nature experiences, such as viewing wild animals, may be difficult to implement in science education, immersive virtual reality (VR) technologies have become a promising tool in education. However, there is limited knowledge regarding the effectiveness of nature experiences in VR. In this study, 50 German university students (M = 23.76 years, SD = 3.73 years) from diverse disciplines were randomly assigned to an immersive (head-mounted display; Oculus Quest) or a nonimmersive setting (external computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 78 publications
5
58
0
2
Order By: Relevance
“…For built environment tasks, invoking a sense of presence may not always be a priority or even feasible when simulations do not have a real-world experiential analogue, such as in cases of scientific data simulations or analysis [30]. At the same time, the sense of presence has been valuable in raising emotional responses and changing attitudes when teaching the effects of climate change and environmental issues [53,54]. In these cases, fully immersive VR configurations such as tracked head-mounted displays or roomlike VR are the most effective in providing viewer-centric embodied experiences.…”
Section: Technology Configurationmentioning
confidence: 99%
“…For built environment tasks, invoking a sense of presence may not always be a priority or even feasible when simulations do not have a real-world experiential analogue, such as in cases of scientific data simulations or analysis [30]. At the same time, the sense of presence has been valuable in raising emotional responses and changing attitudes when teaching the effects of climate change and environmental issues [53,54]. In these cases, fully immersive VR configurations such as tracked head-mounted displays or roomlike VR are the most effective in providing viewer-centric embodied experiences.…”
Section: Technology Configurationmentioning
confidence: 99%
“…21 , p.216). Individuals can take on someone else’s perspective, close the time gap between action and consequences, get interactively involved, receive direct feedback on decisions and behaviour, see consequences, foresee future climate change scenarios, and experience sensory stimulations that can have a strong impact on affections 22 – 26 . The assisting role and the success of technological components in creating a convincing and captivating experience can be subsumed under the term “immersion” 27 , while the engagement of multiple sensory channels has been coined “sensory immersion” 28 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still only limited numbers of virtual nature applications on HMD available, and valid research results for the use of these applications in the various fields of the Sustainable Development Goals (SDGs) are still in the nascent stage 26 . So far, there are only few data on the cognitive, socio-emotional, or behavioural effects of immersive VR technology applied to environmental awareness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When raising emotional responses is a priority, generating a high sense of presence (that is, the feeling of being present in the virtual environment), the level of immersion can be a decisive factor [10,45]. In this regard, Filter et al found immersive experiences to be more effective, raising interest even in people without a positive attitude towards an environmental issue [70]. HMDs and, even more, CAVE technologies can provide a higher sense of presence and emotional arousal compared to desktop displays [71]; however, they are not always an optimal choice.…”
Section: Level Of Immersion Devices and Stimulimentioning
confidence: 99%